Ocena przepływu krwi w tętnicy ocznej i w tętnicy środkowej siatkówki u dzieci z retinopatią wcześniaków - Niwald, Anna; Grałek, Mirosława (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: To evaluate blood flow parameters in the ophthalmic artery and central retinal artery in children with retinopathy of prematurity (ROP). Material and methods: The study comprised 57 premature children born between 24 and 33 weeks of gestation, with birth weight from 600g to 1660g, including 42 preterm children with retinopathy in stage 1, 2, 3 and 3 ,,plus’’ and 15 preterm children without retinopathy. Color Doppler ultrasonography (USG-CD) was used to measure in the studied vessels maximal systolic velocity (Vmax), end-diastolic velocity (Vmin) and resistance index (RI). Results: Statistically significantly (p<0.05) higher values of Vmax were seen in the ophthalmic artery and central retinal artery in preterm children with retinopathy in stage 2 and 3, as compared with other children. In preterms with dilation and tortuosity of posterior blood vessels in stage 3 ,,plus’’ ROP, Vmax in both studied vessels was lower and was comparable to that in stage 1 ROP and in children without retinopathy. RI in the ophthalmic artery in children with ROP in stage 2 and 3 was statistically significantly higher (p<0.05) from its values seen in other groups, and for the central retinal artery RI did not differ statistically significantly. Conclusions: The conducted USG-CD measurements revealed that in children with retinopathy of prematurity haemodynamic parameters of blood flow in the ophthalmic artery and central retinal artery differ in relation to disease stage of advancement, and in relation to the status of blood vessels in the eye fundus. The clinical implications of these results, however, need to be confirmed in long term studies, in order to determine the sensitivity, specificity and repeatability of this method, as well as to establish the diagnostic standards.